2007
DOI: 10.1016/j.exger.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Aging murine B cells have decreased class switch induced by anti-CD40 or BAFF

Abstract: We previously demonstrated that in vitro stimulated splenic B cells from senescent mice are deficient in production of multiple class switch isotypes, class switch recombination (CSR), induction of the E2A-encoded transcription factor E47, and activation-induced cytidine deaminase (AID) which is necessary for CSR and somatic hypermutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…In vitro secreted IgG is reduced with age in both mice (Frasca et al 2007b) and humans (Frasca et al 2008). However, in vivo, despite the reduced number of B cells with age and the defects in class-switching, serum IgG, IgA (but not IgM) are increased with age (Paganelli et al 1992).…”
Section: Consequences Of Senescence On B Cell Functionmentioning
confidence: 94%
“…In vitro secreted IgG is reduced with age in both mice (Frasca et al 2007b) and humans (Frasca et al 2008). However, in vivo, despite the reduced number of B cells with age and the defects in class-switching, serum IgG, IgA (but not IgM) are increased with age (Paganelli et al 1992).…”
Section: Consequences Of Senescence On B Cell Functionmentioning
confidence: 94%
“…It has also been shown to be the key transcription factor in mouse or human B cells undergoing CSR in response to BAFF, the B cell-activating factor, also called BLyS, TALL-1, THANK, ZTNF4, or TNF13B (79 -81). We have recently investigated the ability of BAFF/IL-4, as compared with anti-CD40/IL-4, to induce CSR to ␥ 1 in splenic B cells from young and old mice (82). We found that NF-B is not involved in the decreased response of old B cells to anti-CD40/IL-4.…”
Section: Molecular Mechanisms For the Reduced Activity Of B Cells In mentioning
confidence: 94%
“…Concerning the effects of ageing on the number of immunoglobulin-producing cells in the bone marrow, Speziali et al (2009) have shown that IgG, IgM and IgA immunoglobulin-producing cells were increased in aged mice and these results are coherent with the levels of serum immunoglobulins found, except for IgM that were unaltered in old mice. Frasca et al (2004Frasca et al ( , 2007, have shown that in vitro stimulated splenic B cells from senescent mice are deficient in the production of multiple class switch isotypes and that deficiency is correlated with decreased induction of transcription factor E47, poor activation-induced cytidine deaminase (AID) expression and consequent down-regulation of class switch recombination. As others (Speziali et al, 2009) have reported increased levels of postswitch immunoglobulin isotypes as well as a rise in the number of IgA-and IgG-producing cells in aged mice, it could be speculate that this augment may be due to the proliferation of memory B cells, rather than activation of naïve cells.…”
Section: B Lymphocytesmentioning
confidence: 99%